Anti-diabetic and hypoglycaemic effects of Momordica charantia (bitter melon): a mini review - Leung, Lawrence; Birtwhistle, Richard; Kotecha, Jyoti; Hannah, Susan; Cuthbertson, Sharon (British journal of nutrition, 2009)
It has been estimated that up to one-third of patients with diabetes mellitus use some form of complementary and alternative medicine. Momordica charantia (bitter melon) is a popular fruit used for the treatment of diabetes and related conditions amongst the indigenous populations of Asia, South America, India and East Africa. Abundant pre-clinical studies have documented the anti-diabetic and hypoglycaemic effects of M. charantia through various postulated mechanisms. However, clinical trial data with human subjects are limited and flawed by poor study design and low statistical power. The present article reviews the clinical data regarding the anti-diabetic potentials of M. charantia and calls for better-designed clinical trials to further elucidate its possible therapeutic effects.